PENGAR UH PENYALURAN KREDIT BANK SYARIAH KEPADA USAHA KECIL DAN MENENGAH TERHADAP PENINGKATAN PENDAPATAN DI PROVINSI BANTEN - Chairul Akmal (Al Qalam, 2015)
This paper examines the improvement of credit for Small Micro middle Enterprises (UMKM) given by Sharia Banking in Banten. The method used in this research is survey method that relates to causal statistical descriptive approach. According to the type of data analysis, the research uses quantitative data. Therefore the design of this study is conclusive design that can be descriptive and associative design causal (causal) by which the number of respondents as many as 120 respondents. The result shows that the increasing credit for Small Micro Middle Enterprises (UMKM) given by Sharia Banking in Banten has significantly improved the income of Banten province. The policy has contributed 72.6% of the improvement and other factors contribute only about 27,4%. Key words: Sharia Banking, credit distribution, financial products, Small Micro Middle Enterprises (UMKM), income.